2015
DOI: 10.17576/jsm-2015-4403-12
|View full text |Cite
|
Sign up to set email alerts
|

Lubricity and Tribological Properties of Dicarboxylic Acid and Oleyl Alcohol Based Esters

Abstract: Synthesis of new lubricants nowadays is increasing to improve the lubricity properties

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Therefore, most esters can be worked as boundary lubrication condition. Adsorption of the polar head groups on a metal surface will minimize the surface energy and causes a decrease of the friction coefficient (FC) [60]. In turn, polarity of the biolubricant upsurges its effectiveness in reducing wear.…”
Section: Tribological Analysismentioning
confidence: 99%
“…Therefore, most esters can be worked as boundary lubrication condition. Adsorption of the polar head groups on a metal surface will minimize the surface energy and causes a decrease of the friction coefficient (FC) [60]. In turn, polarity of the biolubricant upsurges its effectiveness in reducing wear.…”
Section: Tribological Analysismentioning
confidence: 99%
“…Considering the poor performance of zinc dibutyldithiophospate as an antiwear additive, the proposed additive failed to achieve equivalent performance to commercially available antiwear additives. Other studies have used biolubricants derived from fatty acids or carboxylic acid and demonstrated improved antiwear performance with the presence of carbonyl groups …”
Section: Introductionmentioning
confidence: 99%
“…The presence of the double bonds and its reactivity have allowed the functional addition reactions into the unsaturated fatty acids. The epoxidation process is one of the most important functionalization reactions of the double bond to other stable functional groups in order to improve the plant oils oxidative stability (Moser & Erhan 2007;Salimon et al 2015Salimon et al , 2011. It is also the most widely industrial used process towards highly unsaturated plant oil to increase their industrial usage (El-Adly et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Epoxidised plant oils products from the epoxidation process can be used as high-temperature lubricants (Lathi & Mattiasson 2007;Salimon et al 2010), plasticizers (Joseph et al 2014) and high temperature coating materials (Derawi & Salimon 2016). Recently, palm oil become one of the potential plant oils in order to produce biolubricant base stock (Salimon & Salih 2009;Salimon et al 2015).…”
Section: Introductionmentioning
confidence: 99%